Internet and distributed computing advancements theoretical frameworks and practical applications - Abawajy, Jemal H.; Pathan, Mukaddim; Rahman, Mustafizur; Pathan, Al-Sakib Khan; Deris, Mustafa Mat (Information Science Reference, 2012)
"This book is a vital compendium of chapters on the latest research within the field of distributed computing, capturing trends in the design and development of Internet and distributed computing systems that leverage autonomic principles and techniques" - Provided by publisher
Includes bibliographical references
Keywords: Datenverarbeitung; Electronic data processing / Distributed processing; Internet; Autonomic computing; Aufsatzsammlung